6098 sayılı Türk Borçlar Kanunu’nun kira sözleşmesine ilişkin genel hükümleri çerçevesinde kira sözleşmesinin sona ermesi - Aydın, Gülşah Sinem (My University, 2013)
Kullandırma amacı güden sözleşmeler arasında yer alan kira sözleşmesi, Türk Hukuku’nda 6098 sayılı Türk Borçlar Kanunu ile düzenlenmiştir. Türk Borçlar Kanunu’nun 299.maddesine göre, “Kira sözleşmesi, kiraya verenin bir şeyin kullanılmasını veya kullanmayla birlikte ondan yararlanılmasını kiracıya bırakmayı, kiracının da buna karşılık kararlaştırılan kira bedelini ödemeyi üstlendiği sözleşmedir.” Çalışmanın içeriğini, Türk Borçlar Kanunu’nun kira sözleşmesine ilişkin genel hükümlerindeki “Sona Erme” başlığı altında, m.327-333 aralığında düzenlenen sona erme halleri oluşturmaktadır. Bu çerçevede belirli süreli kira sözleşmelerinin sürenin geçmesi ile kendiliğinden sona ermesi TBK m.327’de düzenlenmiştir. Belirsiz süreli kira sözleşmelerinin olağan fesih bildirimi yoluyla sona erdirilme düzeni TBK m.328, 329 ve 330 hükümlerinde belirtilmiştir. Devamında “Olağanüstü Fesih” başlığı altında üç sona erme sebebine yer verilmiştir. Bu sebepler; TBK m.331’de düzenlenen önemli sebeplerden ötürü kira sözleşmesinin sona erdirilmesi, TBK m.332’de düzenlenen kiracının iflası halinde kira sözleşmesine son verilmesi ve TBK m.333’de düzenlenen kiracının ölümü üzerine kira ilişkisinin sonlandırılmasıdır.

In Turkish Law, lease contract, which is one of the contracts for the use of property, is regulated by the No. 6098 Turkish Code of Obligations. According to the article 299 of the Turkish Code of Obligations, “Lease contract is a contract that the lease giver leases a property to use or using it with its benefits, and the leaseman claims responsibility for paying rent for that.” The content of the study is constituted by circumstances of termination which are regulated under the title of “Termination” between articles 327 – 333 the general provisions of the lease contract in the Turkish Code of Obligations. In this context, the termination of fixed-term lease contracts with expiration is regulated under the article of 327 in the Turkish Code of Obligations. The order of the termination through the usual termination notice of lease contracts which are based on the indefinite duration, are regulated under the article of 328, 329 and 330 in the Turkish Code of Obligations. In the following articles, three causes of the termination are included under the title of “Extraordinary Termination”. This causes for the termination are; the termination of the lease contract for substantial cause which is regulated under the article of 331, the termination of lease the lease contract in case of bankruptcy of the leaseman which is regulated under the article of 332 and the termination of the lease relationship between the lease giver and the leaseman upon the death of the leaseman which is regulated under the article of 333.
Keywords: Borçlar Hukuku; Kira Sözleşmesi; Özel Hukuk; Türk Borçlar Kanunu